The Barriers to Nurses with Prescriptive Authority in Exercising Their Prescriptive Role: A Systematic Review and Thematic Synthesis of Qualitative Studies - Jiaxi Xu; Lu Qi; Aimei Mao (Global Qualitative Nursing Research)
This systematic review investigates the barriers experienced by nurses with prescriptive authority and their required supports to strengthen and sustain nurse prescribing. Empirical qualitative studies indexed in Embase, MEDLINE, CINAHL, and ProQuest from inception through 31 December 2023 were screened, yielding 27 eligible articles. Data were synthesized with Thomas and Harden’s three-stage inductive approach which included: line-by-line coding, construction of descriptive themes, and generation of analytical themes. Two overarching analytical themes were constructed — “The Undervaluing of Nurse Prescribers” and “The Need for a Supportive System”. Each encompassed several subthemes that expose pervasive misconceptions about, and systemic undervaluation of, nurse prescribers’ expertise. The review underscores the imperative for comprehensive organizational and policy support to strengthen nurse prescribers’ autonomy, confidence, and effectiveness. Because most of the included studies originated from high-income Western countries, future research is needed to examine nurse prescribing in low- and middle-income settings.